Evaluation of frequency of positive exercise-induced bronchospasm between swimmers and sedentary individuals - Mata, Laricy Martins Da; Sanches, Regiane Coissi; Leite, Marceli Rocha; Pacagnelli, Francis Lopes; Vanderlei, Luiz Carlos Marques; Pissulin, Flávio Danilo Mungo (Pontifícia Universidade Católica do Paraná, 2017)
AbstractIntroduction: Despite the prevalence of prescribed asthma, there is uncertainty about the incidence of exercise-induced bronchospasm (EIB).Objective: Compare the frequency of EIB between swimmers and sedentary individuals, and observe heart rate variability during bronchial activity.Methods: In total, 18 swimmers (group 1) and 18 sedentary individuals (group 2) were included. The participants rested for 30 minutes for evaluation of HRV. Blood pressure (PA), respiratory rate (RR), and pulse oxygen saturation (SpO2) were measured. The volunteers remained seated for the spirometry test (maneuver of forced vital capacity - FVC). This was repeated 5, 10, 15, 20, and 30 minutes after the exercise test. The statistical analysis used the Student t, Mann Whitney, and Shapiro-Wilks tests. The significance level was p <0.05.Results: The spirometry findings showed 3 sedentary individuals and 10 swimmers with obstructive ventilatory disorder (OVD). Only 2 of the sedentary and none of the swimmer group demonstrated positive bronchial provocation. A key criterion for diagnosing OVD, the relationship between forced expiratory volume in one second and FVC (FEV1/FVC), was statistically lower in the swimmer group. The measures of the root mean square of the successive differences between adjacent normal RR intervals, in a time interval (RMSSD), and the standard deviation of all normal RR intervals recorded in a time interval (SDNN) were significantly higher among the athletes.Conclusion: The bronchial provocation test identified a higher prevalence of bronchospasm among sedentary individuals. However, there was a reduction in the FEV1/FVC ratio and higher HRV in the group of swimmers.

ResumoIntrodução:Apesar da prevalência da asma definida, há imprecisão sobre incidência de broncoespasmo induzido por exercício (BIE).Objetivo: Comparar a freqüência de BIE entre nadadores e sedentários, e observar a variabilidade da freqüência cardíaca durante a atividade de broncoprovocação.Métodos: Incluídos 18 nadadores (grupo 1) e 18 sedentários (grupo 2). Permaneceram por 30 minutos de repouso para a avaliação da VFC. Foi aferida a pressão arterial (PA), frequência respiratória (f) e a saturação de pulso de oxigênio (SpO2). Permaneceram sentados, para o teste de espirometria (manobra da capacidade vital forçada - CVF). Essa foi repetida em 5, 10, 15, 20 e 30 minutos após o teste de esforço. A análise estatística usou os testes t de Student, Mann Whitney de Shapiro-Wilk, com nível de significância p<0,05.Resultados: A espirometria evidenciou 3 sedentários e 10 nadadores com distúrbio ventilatório obstrutivo (DVO). Apenas 2 do grupo sedentário apresentaram broncoprovocação positiva e nenhum do grupo de nadadores. Um critério fundamental para diagnosticar DVO, a relação entre o volume expiratório no primeiro segundo e a CVF (VEF1/CVF) foi estatisticamente menor no grupo de nadadores. As médias da raiz quadrada da média do quadrado das diferenças entre intervalos RR normais adjacentes, em um intervalo de tempo (RMSSD) e no desvio padrão de todos os intervalos RR normais gravados em um intervalo de tempo (SDNN), foram estatisticamente maiores entre os atletas.Conclusão: O teste de broncoprovocação identificou maior prevalência de broncoespasmo entre os sedentários. Entretanto, houve redução na relação VEF1/CVF e maior VFC no grupo de nadadores.
Avaliação da frequência do broncoespasmo induzido por exercício (BIE) positiva entre nadadores e sedentários
Keywords: Athletes; Asthma; Exercise-Induced Bronchospasm; Atletas; Asma; Broncoespasmo Induzido Por Exercício